A reinterpretation of the Keynesian consumption function and multiplier effect - Ryu-ichiro Murota; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2010)
We propose a microeconomic foundation of the multiplier effect and that of the consumption function using a dynamic optimization model that explains a shortage of aggregate demand and unemployment. We show that government purchases boost aggregate demand through a multiplier-like process but that the implication is quite different. It works through not an increase in disposable income but moderation of deflation, which makes money holding costly and stimulates consumption.
Keywords: E12; E24; E62; 330; Keynesian consumption function; multiplier effect; Keynesian Cross; persistent unemployment; aggregate demand; Konsumtheorie; Keynesianismus; Multiplikator; Langzeitarbeitslosigkeit; Gesamtwirtschaftliche Nachfrage; Theorie